2015
DOI: 10.1007/s12035-015-9295-y
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-9 Regulates Neuronal Circuit Development and Excitability

Abstract: In early postnatal development, naturally occurring cell death, dendritic outgrowth and synaptogenesis sculpt neuronal ensembles into functional neuronal circuits. Here we demonstrate that deletion of the extracellular proteinase MMP-9 affects each of these processes, resulting in maladapted neuronal circuitry. MMP-9 deletion increases the number of CA1 pyramidal neurons, but decreases dendritic length and complexity while dendritic spine density is unchanged. Parallel changes in neuronal morphology are observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 78 publications
(100 reference statements)
2
22
0
1
Order By: Relevance
“…Intercellular adhesion molecule-5 (ICAM-5), which mediates the regulation of dendritic spine elongation and maturation may be cleaved by MMP9 upon activation of N-methyl- d -aspartate (NMDA) receptors [23, 24], suggesting a role for MMP9 in synaptic function. Furthermore, MMP9 deletion increases the number of CA1 pyramidal neurons and decreases the length and complexity of dendritic spines [25]. Immune system dysfunction may develop with aging in parallel with upregulation of brain MMP9 [2628].…”
Section: Discussionmentioning
confidence: 99%
“…Intercellular adhesion molecule-5 (ICAM-5), which mediates the regulation of dendritic spine elongation and maturation may be cleaved by MMP9 upon activation of N-methyl- d -aspartate (NMDA) receptors [23, 24], suggesting a role for MMP9 in synaptic function. Furthermore, MMP9 deletion increases the number of CA1 pyramidal neurons and decreases the length and complexity of dendritic spines [25]. Immune system dysfunction may develop with aging in parallel with upregulation of brain MMP9 [2628].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, MMP‐9 deletion significantly increased spontaneous neuronal activity in awake MMP‐9 knockout mice and enhanced the response to acute pro‐convulsive challenge (Murase et al . ).…”
Section: Research Tools To Study Mmp‐9 In Humans and Animalsmentioning
confidence: 97%
“…In a recent study, Murase et al . () reported that MMP‐9 deletion in mice increased the number of CA1 pyramidal neurons but decreased dendritic length and complexity. Furthermore, parallel changes in neuronal morphology in the primary visual cortex persisted into adulthood.…”
Section: Research Tools To Study Mmp‐9 In Humans and Animalsmentioning
confidence: 98%
“…By the end of the foetal period, PAX6 was gradually down‐regulated, whereas MMP‐9 was increased. In addition to an extensive role during migration, MMP‐9 is important for neurite formation and circuit development that occurs extensively between neurones in the IGL after migration and MMP‐9 is not down‐regulated until this process is completed in mature neurones . The slow‐onset down‐regulation of MMP‐9 seen after exposure to DEX may alter these processes.…”
Section: Discussionmentioning
confidence: 99%